(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with the formation of the customs service. Customs sphere (customs policy and customs business) is one of the real areas and levers that influence the development of the state, it should also affect the integration and globalization processes. This category was used in the industry of Kazakhstan’s customs law, and – in various aspects has been affected in studies of different areas of scientific knowledge both Kazakh and foreign scientists. As is known, the customs policy acts as an integral part of domestic and foreign policy, legislation has defined objectives and mainly economic content. Custom same thing is a kind of means (tools) to achieve the objectives of this policy, with the trends on the simplification of procedures and customs administration. As such, we consider them in custom sphere structure, they can also act under certain conditions as elements customs system. Key words: history of customs service, customs area, customs policy, customs, customs union.